The legal protection of ‘non-indigenous’ minorities under Ethiopia's federal constitution : the case study of Benishangul Gumuz - Maziwisa, Michelle Rufaro (University of Pretoria, 2023)
Mini dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2023.